The impact of physical activity during pregnancy on labour and postpartum period - review - Pliszka , Aleksandra; Michalak , Katarzyna; Jarych , Weronika; Zukierski, Krystian; Mazur , Michał; Żak , Katarzyna; Jucha , Hubert; Madyniak, Katarzyna; Kluz, Agnieszka (Quality in Sport, 2025)
Introduction and Aim: Physical activity significantly impacts quality of life and is recommended at all ages, including time of pregnancy. This study examines the effects of physical activity during pregnancy on the peripartum period, including the risk of labor complications, duration of labor and delivery, the necessity for epidural analgesia, and the incidence of postpartum depression. Methods and Materials: A literature review was conducted using the PubMed, Cochrane Library, and Google Scholar databases. The search included studies published between 2010 and 2025. The search strategy focused on identifying studies describing the effects of physical activity during pregnancy on peripartum outcomes. Keywords used in the search included: "physical activity," "labor and delivery," "exercise," "labor complications," "postnatal depression," and "epidural analgesia." Results and Conclusion: No clear effect of physical activity during pregnancy on the risk of labor complications or the duration of labor was identified. Physical exercise during pregnancy does not reduce the need for epidural analgesia or the risk of postpartum depression. However, regular physical activity during pregnancy decreases the risk of obesity, pregnancy-induced hypertension, and gestational diabetes. Moderate-intensity of the physical activity should be recommended to all pregnant individuals, provided there are no contraindications.